2020
DOI: 10.7717/peerj.9940
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between protein domains and homopeptides in the Plasmodium falciparum proteome

Abstract: The proteome of the malaria parasite Plasmodium falciparum is notable for the pervasive occurrence of homopeptides or low-complexity regions (i.e., regions that are made from a small subset of amino-acid residue types). The most prevalent of these are made from residues encoded by adenine/thymidine (AT)-rich codons, in particular asparagine. We examined homopeptide occurrences within protein domains in P. falciparum. Homopeptide enrichments occur for hydrophobic (e.g., valine), or small residues (alanine or gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
1
0
0
Order By: Relevance
“…However, a non-specific Northern Blot probe hybridizing both endogenous parasite tRNAs and imported host tRNAs showed that, despite their excessive use in protein translation, P. falciparum tRNA Asn does not accumulate more than other tRNAs in the blood stages of the parasite (21). This observation is in line with our hypothesis that insertions, and especially asparagine-rich insertions, could regulate ribosome translation rates and influence protein co-translational folding (22,23). Here, we propose that the import of host tRNA Asn enables the decoding of such asparagine-rich sequences.…”
Section: Discussionsupporting
confidence: 83%
“…However, a non-specific Northern Blot probe hybridizing both endogenous parasite tRNAs and imported host tRNAs showed that, despite their excessive use in protein translation, P. falciparum tRNA Asn does not accumulate more than other tRNAs in the blood stages of the parasite (21). This observation is in line with our hypothesis that insertions, and especially asparagine-rich insertions, could regulate ribosome translation rates and influence protein co-translational folding (22,23). Here, we propose that the import of host tRNA Asn enables the decoding of such asparagine-rich sequences.…”
Section: Discussionsupporting
confidence: 83%